Three Dimensional Elements for Sustainable e-Business Modelling - Dewan, Mohammed Naim Ahmed; Chowdhury Md. Maruf Hossan; Quaddus, Mohammed (International Conference on E-Business, 2012)
e-business modelling is a prevalent term now days as it converts technology into economic value. The sustainability of the business is another global contemporary issue. Although e-business modelling and sustainability are the two major global trends now but still there is no common understanding about the elements that need to be used for a sustainable e-business model. Surprisingly, none of the e-business modelling approaches even consider sustainability as major element. In this paper, therefore, after extensive literature review on e-business modelling and sustainability of the business we carefully identify and determine the required elements for a sustainable e-business model. The elements are three dimensional and selected from customer value area, business value area, and process value area so that the modelling elements safeguard the interests of all stakeholders (customer, business, society, and environment) while maintaining the sustainability.